2019
DOI: 10.3390/horticulturae5020034
|View full text |Cite
|
Sign up to set email alerts
|

LEDs Combined with CHO Sources and CCC Priming PLB Regeneration of Phalaenopsis

Abstract: Throughout this study, the objective was to determine the most effective carbohydrate (CHO) sources under different light-emitting diodes (LEDs), and the impact of chlorocholine chloride (CCC), for the in vitro regeneration of the protocom-like bodies (PLBs) in Phalaenopsis ‘Fmk02010’. We applied 15 LEDs combined with three CHO sources and five CCC concentrations in the study. Organogenesis of PLBs was very poor in maltose both for the number of PLBs and their fresh weight (FW) compared to media containing suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…Sucrose is widely accepted for diverse plant species as the major carbohydrate source to supply the energy to cells in plant tissue culture media [48]. Concentration of sucrose also plant specific for micropropagation, while 20 g/L sucrose is used orchid tissue culture [31,38,[49][50][51], and we confirmed that use of 20 g/L of sucrose can be efficient for the PLB organogenesis of D. okinawense similar to any other Dendrobium sp. (Supplementary Table S1) [6,7].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Sucrose is widely accepted for diverse plant species as the major carbohydrate source to supply the energy to cells in plant tissue culture media [48]. Concentration of sucrose also plant specific for micropropagation, while 20 g/L sucrose is used orchid tissue culture [31,38,[49][50][51], and we confirmed that use of 20 g/L of sucrose can be efficient for the PLB organogenesis of D. okinawense similar to any other Dendrobium sp. (Supplementary Table S1) [6,7].…”
Section: Discussionsupporting
confidence: 75%
“…We previously observed that 20 g/L sucrose is efficient for PLBs organogenesis in orchid plants [31][32][33][34][35][36][37][38]. However, in vitro PLB organogenesis can be plant specific, thereafter, we supplied 0, 5, 10, 20, 30, and 40 g/L of sucrose to the culture media, and five explants in each of 30 ml culture media were cultured for 42 days to compare PLB organogenesis of D. okinawense.…”
Section: Confirmation Of the Sucrose Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…From these observations, it is possible to infer that the absence of light plays an important role in the induction of PLBs, just as light influences the differentiation of PLBs into plantlets. Also, according to [60], the type of light used can also optimize the regeneration of PLBs, with the use of red and white LED combined with sucrose as a carbohydrate source, or blue and white LED with trehalose as the carbohydrate source, which had the best response for the regeneration of PLBs. However, only 17.5% of papers described a dark-period to induce PLBs, while 67.5% used light period (12-16-h photoperiod) to induce and regeneration of PLBs in Phalaenopsis (Table 1).…”
Section: Genus Phalaenopsis and Relatedmentioning
confidence: 99%
“…The last contribution examined is "LEDs Combined with CHO Sources and CCC Priming PLB Regeneration of Phalaenopsis" by Mehraj et al [51]. Regeneration of protocorm-like bodies (PLB) is the best and most efficient technique for orchid micropropagation [52], because it has a rapid proliferation capacity for producing a large number of PLBs within a short period [53].…”
Section: Ornalmental and Medicinal Cropsmentioning
confidence: 99%